Do firm's organisational slacks influence the relationship between corporate lobbying and corporate financial performance? More is not always better - Lin, Woon Leong (MDPI, 2019)
A political involvement in any organisation has often proved to be profitable for such firms that are seeking support and favourable regulatory conditions. Though many studies have investigated the effect of the corporate lobbying activities on the organisations, no clear results have been achieved. In this study, we have investigated the lobbying expenditure of some of the most famous United States (US)-based companies, which support the U.S. government during 2007–2016. Primarily, we tested the relationship between the corporate lobbying and the Corporate Financial Performance (CFP), with the help of a dynamic panel data analysis, which is based on the System Generalised Methods of the Moment (SYS-GMM). The results of this study indicated that the corporate lobbying did not increase the probability of gaining more support from the government in comparison to the firms that did not use any lobbying techniques. Furthermore, the findings showed that corporate lobbying is a component of the zero-sum political agenda that cannot be accurately evaluated and does not contribute towards the improvement of the CFP. This study introduced the important component of organisational slack and noted that the corporate lobbying could significantly destroy the CFP if the organisational slack was high.